The validity of the Graduate Record Examination for master's and doctoral programs: A meta-analytic investigation - KUNCEL, Nathan R. (Institutional Knowledge at Singapore Management University, 2010)
Extensive research has examined the effectiveness of admissions tests for use in higher education. What has gone unexamined is the extent to which tests are similarly effective for predicting performance at both the master’s and doctoral levels. This study empirically synthesizes previous studies to investigate whether or not the Graduate Record Examination (GRE) predicts the performance of students in master’s programs as well as the performance of doctoral students. Across nearly 100 studies and 10,000 students, this study found that GRE scores predict first year grade point average (GPA), graduate GPA, and faculty ratings well for both master’s and doctoral students, with differences that ranged from small to zero.